The role and relevance of garment trading companies as perceived by garment manufacturer - exporters - Decena, Nancy C.
In an era of globalization and advancement of technology, the garment sector faces the challenge of coping up with various changes. In this light, garment manufacturer-exporters assess the service that garment trading offices perform for their companies. A survey among eight garment manufacturer-exporters and five garment trading companies was conducted. Through a questionnaire, the respondents were asked to assess the merchandising functions of trading companies and the available telecommunication facilities that they utilize. Results showed garment manufacturer-exporters still consider the performance trading offices do for them. Inspite of the availability of modern telecommunication facilities and the projected development of direct transaction between manufacturer-exporters and buyers, garment manufacturer-exporters surveyed still place a high regard and value to the role that trading companies play.